3D printing of HEK 293FT cell-laden hydrogel into macroporous constructs with high cell viability and normal biological functions. (18th February 2015) - Ouyang, Liliang; Yao, Rui; Chen, Xi; Na, Jie; Sun, Wei
Abstract: 3D printing has evolved into a versatile technology for fabricating tissue-engineered constructs with spatially controlled cells and biomaterial distribution to allow biomimicking of in vivo tissues. In this paper, we reported a novel study of 3D printing of cell lines derived from human embryonic kidney tissue into a macroporous tissue-like construct. Nozzle temperature, chamber temperature and the composition of the matrix material were studied to achieve high cell viability (>90%) after 3D printing and construct formation. Long-term construct stability with a clear grid structure up to 30 days was observed. Cells continued to grow as cellular spheroids with strong cell–cell interactions. Two transfected cell lines of HEK 293FT were also 3D printed and showed normal biological functions, i.e. protein synthesis and gene activation in responding to small molecule stimulus. With further refinement, this 3D cell printing technology may lead to a practical fabrication of functional embryonic tissues in vitro .